EXPERIENCE WITH THE ANTI-AVALANCHE STRUCTURES IN THE ELBRUS REGION - N. N. Volodicheva (Лëд и снег)
Elbrus region is characterized by the highest degree of avalanche danger, and now the intensive development of winter tourism is coming there. The plan of building protection against avalanches was created here. The snowkeeping shields were built on southern slopes. In winter of 2009, after intensive snowfalls, the shields were partial covered with avalanche snow, but they did not let the bigger avalanches to form. The builders did not consider the complexity of avalanche structure and made some mistakes in the sequence of shields building. The distribution of snow cover on slopes, the dominant avalanche genetic types that define the volume, speed, and the power of blow and the range of emission must be considered during the designing and building of avalanche protection systems. The experience of MSU works must be used during the building of avalanche protection systems in others places of Elbrus region.